Mechanical and tribological characterization of industrial wastes reinforced aluminum alloy composites fabricated via friction stir processing - Kumar, H.; Prasad, R.; Kumar, P.; Tewari, S.P.; Singh, J.K. (Elsevier Ltd, 2020)
The fabrication of particulate reinforced metal matrix composites via melt based processes poses issues like aggregation, wettability and formation of detrimental phases which may severely affect their performance. Recently developed solid-state process i.e., friction stir processing (FSP), is an efficient fabrication technique to counter the limitations of melt based processes. However, the incorporation of industrial waste in the metal matrix by using friction stir processing is rarely reported. Thus, the present investigation was carried out to reinforce the particulate type industrial waste in cast A356 alloy by friction stir processing. The performance of the fabricated composites as well as the as-cast A356 alloy was assessed through mechanical and tribological characterization. It was observed that FSP resulted in the eradication of porosity, fragmentation of α-Al dendrites, breakage and redistribution of Si particles, and grain refinement. A fair homogeneous distribution of reinforcement was observed in stir zone (SZ) with negligible aggregation of particulate reinforcement. The particle/matrix interface was free from any detrimental phase. The improvement in strength, ductility, and wear resistance was observed as compared to as-cast A356 alloy which was attributed to the microstructural changes that occurred during FSP, and the efficient reinforcement of particles via FSP. © 2020 Elsevier B.V.
Keywords: Friction stir processing; Microstructure; Hardness; Strength; Ductility; Wear